Transformation of the Oral Tradition of Javanese Dolanan Songs in the Gresik Community - Khoiro, Septiani Limatul; Budiati, Atik Catur; Ghufronudin, Ghufronudin Ghufronudin (JUPE : Jurnal Pendidikan Mandala, 2023)
This study aims to analyse the transformation of oral tradition development including the form of transformation and the impact of transformation on Gresik society. This research uses a descriptive qualitative approach with a case study strategy by focusing on the subject under study. Data sources consist of primary data which includes interviews and observations of the religious tourism environment in Gresik Regency. While secondary data comes from documentation including literature studies, archival documents of “tembang dolanan” and religious tourism profiles of Gresik Regency. The technique of taking informants using snowball sampling is by selecting key informants from traditional leaders, local government officials, the surrounding community and elementary school students. Data validity using source triangulation by presenting the findings of one then combined with other data findings. Data analysis uses four components, namely data collection, data reduction, data presentation, conclusion drawing and verification. The results showed that the forms of “tembang dolanan” transformation are changes in function, socialisation media, and lyric modification. These three changes go hand in hand with the changing times so that its existence still exists in Gresik society. While the impact of the transformation becomes learning material in schools, a means of creativity to accompany children's games and praise, and becomes a cultural heritage of oral tradition in Gresik society. Changing mindsets, cultural values, changing generations and technological developments are the main factors in this transformation process.